DAMPAK DESENTRALISASI FISKAL TERHADAP EFISIENSI BELANJA PEMERINTAH DAERAH DAN KINERJA SEKTOR PUBLIK (STUDI EMPIRIS WILAYAH BANJARNEGARA, PURBALINGGA, BANYUMAS, & CILACAP) - suharno *; Lilis Siti Badriah* (Jurnal Ekonomi Bisnis dan Akuntansi (JEBA), 2011)
ABSTRACTObject of this study are Banjarnegara Regency, PurbalinggaRegency, BanyumasRegency, & Cilacap Regency.Improved efficiency is the main effect expected from fiscal decentralization. It could be gained on the presumptions that local governments are much better in identifying and fulfilling local public preferences, since they are closer to them, and in mobilizing and using local resources to pay for goods and services having purely local impacts. Once improved efficiency could be gained, public sector performance increase. I developed a model to measure public sector efficiency (PSE) and public sector performance (PSP). (Kurnia, 2006).I compute public sector performance (PSP) and Public Sector Efficiency (PSE) indicators comprising a composite consists of five sub-indicators. The first two indicators reflects socio-economic indicators that take into account education and health outcomes. Three other indicators reflect the standard “musgravian” task for government: allocation, distribution and stabilization. Then, the model is applied to measure public sector performance and efficiency of Regency in Banjarnegara, Purbalingga, Banyumas, & Cilacap  Central Java ProvinceKeywords : Fiscal Decentralization, Public Sector Efficiency (PSE), Public Sector Performance (PSP), Data envelopment Analysis (DEA).